2015
DOI: 10.1016/j.numecd.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and incidence of metabolic syndrome

Abstract: Background and aims: Whether iron metabolism affects metabolic syndrome (METS) is debated. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(47 reference statements)
2
12
1
Order By: Relevance
“…In accordance, 2 studies have shown transferrin to be associated with higher fasting insulin and 2‐h glucose concentrations but not with fasting glucose concentrations, similar to our study. Further, in our study, transferrin showed borderline positive associations with IGM and MetS, but not with T2DM, although positive associations have been reported elsewhere 5,16,23,37 . Despite its inverse correlation with ferritin, positive associations of transferrin with metabolic outcomes probably suggest iron‐independent pathways 5 .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In accordance, 2 studies have shown transferrin to be associated with higher fasting insulin and 2‐h glucose concentrations but not with fasting glucose concentrations, similar to our study. Further, in our study, transferrin showed borderline positive associations with IGM and MetS, but not with T2DM, although positive associations have been reported elsewhere 5,16,23,37 . Despite its inverse correlation with ferritin, positive associations of transferrin with metabolic outcomes probably suggest iron‐independent pathways 5 .…”
Section: Discussioncontrasting
confidence: 58%
“…Additional investigations of transferrin may help to further understand the role of iron in the pathogenesis of metabolic disorders. However, studies investigating the relation between transferrin and IGM, T2DM or MetS, in addition to ferritin are sparse 5,8,15,16 . Hence, there is only weak and inconsistent evidence to support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Korean adolescents also found that serum ferritin levels ((the concentration of ferritin in the study was 42.7 (40.7,44.9) µg/L) were negatively associated with HDL-C values, even after adjusting for all covariates [41]. One possible reason is that, unlike other reports [17,42,43], the distribution of iron storage indicators in these studies is within the normal range. The definition of iron surplus of TBI is beyond zero [29].…”
Section: Discussionmentioning
confidence: 50%
“…Currently, there is controversy on the association of iron concentrations in the body and its metabolism with the development of the MetS in both genders, both in adults and adolescents. Iron is usually considered as an independent factor for the development of MetS and, thus, not in all cases associated with ceruloplasmin levels [36][37][38][39][40][41].…”
Section: Non Mets Metsmentioning
confidence: 99%